Composite sulfide-based solid electrolyte and its manufacturing method
The composite sulfide-based solid electrolyte, featuring lithium halide between primary particles, enhances moisture resistance and maintains high ionic conductivity, overcoming the manufacturing and stability challenges of conventional sulfide-based solid electrolytes.
Patent Information
- Application Number
- JP2024553485
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-15
- Filing Date
- 2023-11-22
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-11-22
AI Technical Summary
Conventional sulfide-based solid electrolytes require strict handling conditions due to low chemical stability and are prone to moisture-induced reactions, which reduce ionic conductivity and complicate large-scale manufacturing and mass production of all-solid-state batteries.
A composite sulfide-based solid electrolyte is developed by mixing lithium halide with a sulfide-based solid electrolyte, forming secondary particles where lithium halide is located between the primary particles. This configuration enhances moisture resistance and maintains high ionic conductivity.
The composite sulfide-based solid electrolyte improves moisture resistance, prevents reduction in ionic conductivity, and facilitates easier large-scale manufacturing and mass production of all-solid-state batteries, addressing the challenges faced by conventional sulfide-based solid electrolytes.
Smart Images

Figure 2025511504000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0176307 dated December 15, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a composite sulfide-based solid electrolyte and a method for producing the same. [Background technology]
[0003] 2. Description of the Related Art As the demand for electric vehicles and large-capacity power storage devices increases, various secondary batteries have been developed to meet this demand.
[0004] Lithium secondary batteries have the best energy density and output characteristics among various secondary batteries, and have been widely commercialized. As lithium secondary batteries, lithium secondary batteries containing liquid-type electrolytes containing organic solvents (hereinafter referred to as "liquid-type secondary batteries") are mainly used.
[0005] However, it has been pointed out that liquid-type secondary batteries have a risk of causing the battery to expand when the liquid electrolyte is decomposed by the electrode reaction, and that there is a risk of fire due to leakage of the liquid electrolyte. In order to solve these problems of liquid-type secondary batteries, lithium secondary batteries that use a highly stable solid electrolyte (hereinafter referred to as "all-solid-state batteries") have attracted attention.
[0006] Solid electrolytes are broadly divided into polymer electrolytes, oxide solid electrolytes, and sulfide solid electrolytes. Sulfide solid electrolytes are softer than oxide solid electrolytes, and therefore can provide excellent interparticle contact properties even with room temperature compression without a separate sintering process. As a result, sulfide solid electrolytes have attracted attention because they have lower contact resistance and higher ionic conductivity than oxide solid electrolytes.
[0007] However, sulfide-based solid electrolytes have a drawback in that their chemical stability is relatively lower than that of oxide-based solid electrolytes, and therefore their stability is reduced when applied to all-solid-state batteries. That is, sulfide-based solid electrolytes are prone to react with moisture in the air or moisture introduced during processing due to various factors such as L2S and P2S7 bridging sulfur remaining in the electrolyte. As a result, sulfide-based solid electrolytes are handled in environments such as glove boxes with an argon gas atmosphere or dry rooms where moisture has been removed, as they may react with moisture and generate hydrogen sulfide (H2S) gas. Furthermore, sulfide-based solid electrolytes have problems in the manufacturing process, such as a decrease in ion conductivity due to the influence of hydrogen sulfide gas generated by reaction with moisture.
[0008] As described above, conventional sulfide-based solid electrolytes require strict handling conditions, and therefore, when manufacturing all-solid-state batteries using sulfide-based solid electrolytes, it is currently difficult to increase the area and mass-produce them. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Korean Patent Publication No. 2019-0079135 Summary of the Invention [Problem to be solved by the invention]
[0010] An object of the present invention is to provide a composite sulfide-based solid electrolyte that can improve the moisture resistance of the solid electrolyte and prevent a decrease in ion conductivity due to long-term exposure to moisture during the manufacture of an all-solid-state battery by forming a composite sulfide-based solid electrolyte in the form of secondary particles by mixing a lithium halide with a sulfide-based solid electrolyte.
[0011] Another object of the present invention is to provide a method for producing the composite sulfide-based solid electrolyte. [Means for solving the problem]
[0012] One embodiment of the present invention provides a composite sulfide-based solid electrolyte, the secondary particles including a plurality of primary particles and a lithium halide represented by the following Chemical Formula 1, the primary particles including a sulfide-based solid electrolyte, and the lithium halide being located between the primary particles. [Chemical formula 1] LiX In the above formula 1, X is any one selected from F, Cl, Br and I.
[0013] The lithium halide may have an average particle size (D50) of 0.01 to 3 μm.
[0014] The average particle size (D50) of the secondary particles of the composite sulfide-based solid electrolyte may be 0.11 to 100 μm.
[0015] Based on a total of 100 parts by weight of the composite sulfide-based solid electrolyte, the content ratio of the sulfide-based solid electrolyte and lithium halide in the primary particles may be 99.9 parts by weight:0.1 parts by weight to 80 parts by weight:20 parts by weight.
[0016] The sulfide-based solid electrolyte may include an argyrodite-type crystal structure.
[0017] The average particle size (D50) of the primary particles may be 0.1 to 15 μm.
[0018] In the composite sulfide-based solid electrolyte of the secondary particles, the lithium halide may not be formed as a coating layer of the primary particles.
[0019] The primary particle sulfide-based solid electrolyte may be represented by the following Chemical Formula 2. [Chemical formula 2] Li k M 1 l S m X 1 n In the above Chemical Formula 2, M 1is Sn, Mg, Ba, B, Al, Ga, In, Si, Ge, Pb, N, P, As, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W, or La, and X 1 is F, Cl, Br, I, Se, Te, or O, where 0 < k ≤ 6, 0 < l ≤ 6, 0 < m ≤ 6, and 0 ≤ n ≤ 6.
[0020] Another embodiment of the present invention provides a all-solid-state battery including the composite sulfide-based solid electrolyte.
[0021] Another embodiment of the present invention provides a method for manufacturing a composite sulfide-based solid electrolyte, including the steps of preparing a sulfide-based solid electrolyte and lithium halide represented by the following Chemical Formula 1; pulverizing the lithium halide; and mixing the pulverized lithium halide and the sulfide-based solid electrolyte. [Chemical Formula 1] LiX In Chemical Formula 1, X is any one selected from F, Cl, Br, and I.
[0022] Before pulverizing the lithium halide, the method may further include a step of vacuum drying to remove moisture of the lithium halide.
[0023] The lithium halide may be formed by pulverizing through ball-milling at 100 to 2,000 rpm for 5 to 30 minutes as one cycle, and repeating the ball-milling 5 to 20 cycles.
[0024] The average particle diameter (D50) of the pulverized lithium halide may be 0.01 to 3 μm.
[0025] The pulverized lithium halide and the sulfide-based solid electrolyte may be mixed at a content ratio of 99.9 parts by weight: 0.1 part by weight to 80 parts by weight: 20 parts by weight based on 100 parts by weight of the total composite sulfide-based solid electrolyte. Effect of the Invention
[0026] According to the present invention, a composite sulfide-based solid electrolyte in the form of secondary particles is formed such that lithium halide particles having a relatively small size are located in spaces between primary particles of the sulfide-based solid electrolyte, thereby improving the moisture resistance of the solid electrolyte and preventing a decrease in ionic conductivity of the all-solid-state battery. [Brief description of the drawings]
[0027] [Figure 1] FIG. 1 is a schematic diagram of a composite sulfide-based solid electrolyte according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of a sulfide-based solid electrolyte not containing lithium halide according to a comparative example of the present invention. [Diagram 3] 1 is a scanning electron microscope (SEM) image of a composite sulfide-based solid electrolyte according to an embodiment of the present invention. [Figure 4] 1 is an image showing an energy dispersive X-ray spectroscopy (EDX) analysis result of a composite sulfide-based solid electrolyte according to an embodiment of the present invention. [Diagram 5] 1 is an image showing an energy dispersive X-ray spectroscopy (EDX) analysis result of a composite sulfide-based solid electrolyte according to an embodiment of the present invention. [Figure 6] 1 is a graph showing a change in ionic conductivity over time of a composite sulfide-based solid electrolyte according to an embodiment of the present invention. [Figure 7] 1 is a graph showing a change in normalized ionic conductivity over time of a composite sulfide-based solid electrolyte according to an embodiment of the present invention. [Figure 8]1 is a graph showing an EIS (Electrochemical Impedance Spectroscopy) analysis of lithium halide (LiBr). [Figure 9] 1 is a graph showing an EIS (Electrochemical Impedance Spectroscopy) analysis of Li6PS5Cl, a sulfide-based solid electrolyte having an argyrodite crystal structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Hereinafter, the embodiments of the present invention will be described in detail. Prior to this, the terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as meanings and concepts that correspond to the technical ideas of the present invention, based on the principle that the inventor can appropriately define the concepts of terms in order to best describe his / her invention. Therefore, since the configurations described in the embodiments described in this specification are merely the most preferred embodiments of the present invention and do not fully represent the technical ideas of the present invention, it should be understood that there are various equivalents and modifications that can replace them at the time of this application.
[0029] Throughout this specification, when a part is said to "comprise" certain elements, this means that it can further include other elements, rather than excluding other elements, unless specifically stated to the contrary.
[0030] Furthermore, descriptions that specify or limit components or add elements can be applied to all inventions unless otherwise specified, and are not limited to a particular invention.
[0031] Moreover, throughout the description and claims of this application, the singular includes the plural, unless specifically stated otherwise.
[0032] Furthermore, throughout the description of the invention and claims of this application, unless otherwise stated, "or" includes "and." Therefore, "including A or B" means all three cases of including A, including B, or including both A and B.
[0033] Additionally, all numerical ranges include the endpoints and all intermediate values therebetween unless expressly stated to be excluded.
[0034] Throughout this specification the average particle size of the particles may be the median diameter (D50) measured, for example, using a laser particle size analyzer.
[0035] Hereinafter, a composite sulfide-based solid electrolyte according to an embodiment of the present invention will be described.
[0036] The present invention relates to a composite sulfide-based solid electrolyte that can improve the moisture resistance of a solid electrolyte, prevent a decrease in ion conductivity of an all-solid-state battery due to the influence of external moisture during the manufacture of the all-solid-state battery, and improve electrochemical and life characteristics, and a manufacturing method thereof.
[0037] Generally, sulfide-based solid electrolytes have the advantage that they can achieve excellent contact between particles, low contact resistance, and high ionic conductivity without a separate sintering process, all by applying pressure at room temperature. However, they tend to react with moisture in the air or moisture introduced during the manufacturing process to generate hydrogen sulfide (H2S) gas, which can reduce the ionic conductivity, which is a key characteristic of solid electrolytes.
[0038] In order to solve this problem, there have been attempts to form a coating layer on the surface of sulfide-based solid electrolyte particles to block reactions with moisture, but this results in a problem that the material contained in the coating layer acts as a resistance layer and further reduces the ionic conductivity of the solid electrolyte.
[0039] In order to solve the above problems, the present invention has been made by mixing a sulfide-based solid electrolyte, which is a primary particle, with lithium halide to form a secondary particle-type solid electrolyte, instead of forming a separate coating layer on sulfide-based solid electrolyte particles. In particular, the lithium halide is positioned between the vacant spaces of the primary particles of the sulfide-based solid electrolyte, whereby the lithium halide functions to adsorb external moisture, improving the moisture resistance of the sulfide-based solid electrolyte, reducing the generation of hydrogen sulfide, and exhibiting high ionic conductivity. This has led to the completion of the present invention.
[0040] FIG. 1 is a schematic diagram showing a composite sulfide-based solid electrolyte according to one embodiment of the present invention.
[0041] Referring to FIG. 1, a composite sulfide-based solid electrolyte according to an embodiment of the present invention is a secondary particle including a plurality of primary particles and a lithium halide represented by the following Chemical Formula 1, wherein the primary particles include a sulfide-based solid electrolyte, and the lithium halide may be located between the primary particles. [Chemical formula 1] LiX In the above formula 1, X is any one selected from F, Cl, Br and I.
[0042] That is, the lithium halide is not formed as a coating layer on the primary particles of the sulfide-based solid electrolyte, but is located between the primary particles of the sulfide-based solid electrolyte, thereby adsorbing external moisture and improving the moisture resistance of the sulfide-based solid electrolyte. For example, the lithium halide represented by Chemical Formula 1 may be LiF, LiCl, LiBr, or LiI, and preferably may be LiBr.
[0043] 8 and 9 are graphs showing EIS (Electrochemical Impedance Spectroscopy) analyses of lithium halide (LiBr) and sulfide-based solid electrolytes with argyrodite crystal structure, respectively.
[0044] 8 and 9, the sulfide-based solid electrolyte with an argyrodite crystal structure exhibits high ionic conductivity of 0.1 mS / cm or more, whereas the lithium halide LiBr exhibits a self-ionic conductivity of 9.62×10 as can be seen from the EIS measurement results at 25°C in FIG. 8. -6 Since the resistivity (S / cm) of the sulfide-based solid electrolyte is very low, it can act as a very large resistance layer when applied to a sulfide-based solid electrolyte.
[0045] Therefore, if lithium halide is formed as a surface coating layer on the surface of a sulfide-based solid electrolyte as shown in FIG. 2, regardless of the moisture adsorption performance of lithium halide, the resistance at the grain boundaries of lithium halide is too high, resulting in a problem that ion conduction between sulfide-based solid electrolyte particles is difficult.
[0046] In contrast, the composite sulfide-based solid electrolyte according to an embodiment of the present invention has the advantage that it is possible to prevent an increase in internal resistance by not forming a separate lithium halide coating layer on the sulfide-based solid electrolyte particles, and to provide sufficient moisture resistance by disposing the lithium halide between the primary particles of the sulfide-based solid electrolyte. In addition, by including the lithium halide as fine particles having an average particle size of 0.01 to 3 μm, the lithium ions (Li + ) will not be significantly hindered.
[0047] Referring to a method for producing a composite sulfide-based solid electrolyte according to an embodiment of the present application, the lithium halide according to an embodiment of the present application may be subjected to a pulverization process using a ball mill or the like before being mixed with a sulfide-based solid electrolyte. In an embodiment of the present invention, the lithium halide may have an average particle size (D50) of 0.01 to 3 μm, for example, 0.01 to 1 μm, 0.01 to 0.5 μm, or preferably 0.01 to 0.1 μm.
[0048] If the average particle size of the lithium halide is less than 0.01 μm, it may be difficult to maintain a small particle state, and the manufacturing process of the secondary particle type composite sulfide-based solid electrolyte may become complicated. If it exceeds 3 μm, the specific surface area of the lithium halide particles may relatively decrease, and the effect of improving the moisture resistance of the composite sulfide-based solid electrolyte may decrease.
[0049] The lithium halide is not limited in shape, and may be in any shape, such as, but not limited to, a spherical shape, a plate shape, a pyramidal shape, a cylindrical shape, etc. The average particle size of the lithium halide may have different meanings depending on the shape, and may be, for example, the diameter of the sphere in the case of a sphere, and the diameter of the major axis or the minor axis in the case of an ellipse.
[0050] In one embodiment of the present invention, the average particle size (D50) of the secondary particles of the composite sulfide-based solid electrolyte may be 0.11 to 100 μm, for example, 0.2 to 80 μm, 0.3 to 70 μm, 0.4 to 60 μm, 0.5 to 50 μm, 0.6 to 40 μm, 0.7 to 40 μm, 0.8 to 30 μm, 0.9 to 25 μm, or 1 to 20 μm.
[0051] If the average particle size of the secondary particles of the composite sulfide-based solid electrolyte is less than 0.11 μm, the lithium ion conductivity and moisture resistance of the solid electrolyte may be significantly reduced, and if it exceeds 100 μm, problems may occur in the process of forming a solid electrolyte membrane when preparing an all-solid-state battery using the solid electrolyte.
[0052] In one embodiment of the present invention, based on a total of 100 parts by weight of the composite sulfide-based solid electrolyte, the content ratio of the sulfide-based solid electrolyte of the primary particles to lithium halide may be 99.9 parts by weight:0.1 parts by weight to 80 parts by weight:20 parts by weight, for example, 99.5 parts by weight:0.5 parts by weight to 85 parts by weight:15 parts by weight, 99 parts by weight:1 part by weight to 90 parts by weight:10 parts by weight, preferably 99 parts by weight:1 part by weight to 92.5 parts by weight:7.5 parts by weight.
[0053] If the content of lithium halide is less than 0.1 parts by weight based on a total of 100 parts by weight of the composite sulfide-based solid electrolyte, the adsorption ability for external moisture, i.e., the moisture resistance of the composite sulfide-based solid electrolyte, may decrease, and the ion conductivity of the solid electrolyte may decrease due to the generation of hydrogen sulfide gas, etc. If the content of lithium halide exceeds 20 parts by weight, the content of primary particles of the sulfide-based solid electrolyte in the composite sulfide-based solid electrolyte may relatively decrease, resulting in a problem of a decrease in lithium ion conductivity of the electrolyte.
[0054] In one embodiment of the present invention, the average particle size (D50) of the primary particles of the composite sulfide-based solid electrolyte may be 0.1 to 15 μm, for example, 0.2 to 15 μm, 0.3 to 10 μm, or preferably 0.5 to 5 μm.
[0055] If the average particle size of the primary particles of the composite sulfide-based solid electrolyte is less than 0.1 μm, the lithium ion conductivity and moisture resistance of the solid electrolyte may be significantly reduced. If the average particle size of the primary particles of the composite sulfide-based solid electrolyte is more than 15 μm, the size of the secondary particles of the composite sulfide-based solid electrolyte containing the composite sulfide-based solid electrolyte may relatively increase, which may cause problems in the process of forming a solid electrolyte membrane when preparing an all-solid-state battery using the solid electrolyte.
[0056] In one embodiment of the present invention, the primary particle sulfide-based solid electrolyte may be represented by the following Chemical Formula 2. [Chemical formula 2]
[0057] Li k M 1 l S m X 1 n In the above Chemical Formula 2, M 1 is Sn, Mg, Ba, B, Al, Ga, In, Si, Ge, Pb, N, P, As, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W, or La; 1is F, Cl, Br, I, Se, Te, or O, where 0 < k ≤ 6, 0 < l ≤ 6, 0 < m ≤ 6, and 0 ≤ n ≤ 6.
[0058] For example, in Chemical Formula 2, M 1 can be B, Si, Ge, P, or N.
[0059] For example, in Chemical Formula 2, X 1 can be F, Cl, Br, I, or O.
[0060] For example, the sulfide-based solid electrolyte represented by Chemical Formula 2 is Li2S-P2S5, Li2S-P2S5-LiX, where X is a halogen element, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n , m, n are positive numbers, Z is any one of Ge, Zn, or Ga, Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q , p, q are positive numbers, M is any one of P, Si, Ge, B, Al, Ga, In, Li 7-x PS 6-x Cl x , 0 ≤ x ≤ 2, Li 7-x PS 6-x Br x , 0 ≤ x ≤ 2, and Li 7-x PS 6-x I x may be one or more selected from 0 ≤ x ≤ 2.
[0061] Also, preferably, the sulfide-based solid electrolyte may be a solid electrolyte having an argyrodite crystal structure containing one or more selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I.
[0062] The composite sulfide-based solid electrolyte according to the present invention can be produced by the following production method. Each step of the production method for the sulfide-based solid electrolyte according to the present invention will be specifically described below.
[0063] First, in order to prepare a composite sulfide-based solid electrolyte according to the present invention, a sulfide-based solid electrolyte and a lithium halide represented by the following Chemical Formula 1 are prepared. [Chemical formula 1] LiX (In the above Chemical Formula 1, X is any one selected from F, Cl, Br and I).
[0064] The sulfide-based solid electrolyte and the lithium halide represented by Formula 1 are the same as those described above, and therefore, detailed description thereof will be omitted below.
[0065] The lithium halide is then pulverized to form fine particles.
[0066] The step of pulverizing the lithium halide may not be limited to a specific method, and may be performed by ball milling for 5 to 20 cycles, with ball milling at 100 to 2,000 rpm for 5 to 30 minutes being one cycle. If the ball milling speed and time are below the above ranges, the empty spaces between the primary particles of the sulfide-based solid electrolyte, which are the primary particles, may not be filled well, and the effect of improving the moisture resistance of the sulfide-based solid electrolyte may be insignificant. If the speed and time are above the above ranges, the manufacturing process time and cost of the solid electrolyte may increase, and excessive heat may occur.
[0067] In order to further increase the moisture adsorption ability of the lithium halide, preferably, the method may further include a step of vacuum drying the lithium halide to remove moisture from the lithium halide before pulverizing the lithium halide. Although not limited to a specific method, the lithium halide before pulverization may be preliminarily subjected to a process of being loaded into a vacuum oven and dried at a temperature of 25 to 80° C. for 24 to 48 hours.
[0068] The lithium halide pulverized using a ball mill or the like as described above may have an average particle size (D50) of 0.01 to 3 μm.
[0069] Finally, the sulfide-based solid electrolyte and the pulverized lithium halide are mixed to form a composite sulfide-based solid electrolyte in the form of secondary particles in which the lithium halide in the form of fine particles is located between the primary particles of the sulfide-based solid electrolyte.
[0070] In one embodiment of the present invention, the primary particles of the sulfide-based solid electrolyte and the lithium halide may be mixed in a ratio of 99.9 parts by weight:0.1 parts by weight to 80 parts by weight:20 parts by weight, for example, 99.5 parts by weight:0.5 parts by weight to 85 parts by weight:15 parts by weight, 99 parts by weight:1 part by weight to 90 parts by weight:10 parts by weight, preferably 99 parts by weight:1 part by weight to 92.5 parts by weight:7.5 parts by weight, based on a total of 100 parts by weight of the composite sulfide-based solid electrolyte.
[0071] The present invention also provides an all-solid-state battery including the composite sulfide-based solid electrolyte, the all-solid-state battery including a positive electrode, a negative electrode, and a solid electrolyte membrane, at least one of the positive electrode, the negative electrode, and the solid electrolyte membrane may include the composite sulfide-based solid electrolyte having the above-mentioned characteristics.
[0072] In one embodiment of the present invention, the solid electrolyte membrane is an ion-conductive sheet that is interposed between a positive electrode and a negative electrode in an all-solid-state battery and acts as an insulation and an ion-conductive channel, and preferably has a conductivity of 1.0×10 -5 The solid electrolyte membrane may include the composite sulfide-based solid electrolyte according to the present invention, and may further include other electrolyte materials described below.
[0073] In the present invention, the positive electrode and the negative electrode each have a current collector and an electrode active material layer formed on at least one surface of the current collector, and the active material layer contains a plurality of electrode active material particles and an electrolyte material. The positive electrode and the negative electrode can include the composite sulfide-based solid electrolyte according to the present invention as the electrolyte material, and can further include, in addition, other electrolyte materials to be described later.
[0074] Further, each of the electrodes can further include one or more of a conductive material and a binder resin, as necessary. Further, the electrode can further include various additives for the purpose of complementing and improving the physicochemical properties of the electrode.
[0075] In the present invention, as the negative electrode active material, lithium metal can be included as the negative electrode active material of a lithium ion secondary battery, and any material that can be used as the negative electrode active material can be used. For example, the negative electrode active material includes carbon such as graphitizable carbon and graphite-based carbon; Li x Fe2O3(0≦x≦1), Li x WO2(0≦x≦1), Sn x Me 1-x Me′ y O z (Me: Mn, Fe, Pb, Ge; Me′: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) and other metal composite oxides; lithium alloys; silicon-based alloys; tin-based alloys; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides, etc. One or more selected therefrom may be further included.
[0076] When the electrode is a positive electrode, the electrode active material can be used without limitation as long as it can be used as a positive electrode active material for a lithium ion secondary battery. For example, the positive electrode active material can be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; 1+x Mn 2-x Lithium manganese oxides such as LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-x M x O2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x=0.01-0.3); 1-x M x Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M=Co, Ni, Fe, Cr, Zn or Ta, and x=0.01 to 0.1) or Li2Mn3MO8 (wherein M=Fe, Co, Ni, Cu or Zn); LiNi x Mn 2-x Examples of the lithium manganese oxide include, but are not limited to, lithium manganese oxides having a spinel structure represented by the formula LiMn2O4, in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion, disulfide compounds, and Fe2(MoO4)3.
[0077] In the present invention, the current collector is an electrically conductive material such as a metal plate, and any suitable material known in the field of secondary batteries can be used depending on the polarity of the current collector electrode.
[0078] In the present invention, the conductive material is usually added in an amount of 1% by weight to 30% by weight based on the weight of the entire mixture including the electrode active material. Such a conductive material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may include one or a mixture of two or more conductive materials selected from graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, and other carbon black-based carbon materials; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and polyphenylene derivatives.
[0079] In the present invention, the binder resin is not particularly limited as long as it is a component that assists in binding between the active material and the conductive material and the current collector, and examples thereof include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber, fluororubber, various copolymers, etc. The binder resin may usually be contained in a range of 1 wt % to 30 wt % or 1 wt % to 10 wt % relative to 100 wt % of the electrode layer.
[0080] Meanwhile, in the present invention, each of the electrode active material layers may contain one or more additives such as an oxidation stabilizing additive, a reduction stabilizing additive, a flame retardant, a heat stabilizer, an antifogging agent, etc., if necessary.
[0081] In the present invention, the all-solid-state battery may include the composite sulfide-based solid electrolyte according to the present invention as a solid electrolyte material, and may further include at least one of a polymer-based solid electrolyte, an oxide-based solid electrolyte, and a sulfide-based solid electrolyte.
[0082] The polymer solid electrolyte is a composite of lithium salt and polymer resin, i.e., a polymer electrolyte material formed by adding polymer resin to a solvated lithium salt. -7 S / cm or more, preferably about 1×10 -5 It can exhibit ionic conductivity of more than S / cm.
[0083] Non-limiting examples of the polymer resin include polyether polymers, polycarbonate polymers, acrylate polymers, polysiloxane polymers, phosphazene polymers, polyethylene derivatives, alkylene oxide derivatives such as polyethylene oxide, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ionic dissociation groups, etc., and the polymer electrolyte may include at least one of them. In addition, examples of the polymer resin of the polymer electrolyte include branched copolymers in which amorphous polymers such as PMMA, polycarbonate, polysiloxane (pdms) and / or phosphazene are copolymerized with a comonomer on a PEO (polyethylene oxide) main chain, comb-like polymers, and crosslinked polymer resins, and the like, and the polymer electrolyte may include at least one of them.
[0084] In the electrolyte of the present invention, the above-mentioned lithium salt is Li + X - The anion of such a lithium salt is not particularly limited, but may be F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF -, (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , (CF3CF2SO2)2N - The following can be given as examples:
[0085] The oxide-based solid electrolyte material contains oxygen (O) and has the ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table. Non-limiting examples of this include LLTO-based compounds, Li6La2CaTa2O 12 , Li6La2ANb2O 12 (A is Ca or Sr), Li2Nd3TeSbO 12 , LiBO 2.5 N 0.5 , Li9SiAlO8, LAGP compounds, LATP compounds, Li 1+x Ti 2-x Al x S y (PO4) 3-y (where 0≦x≦1, 0≦y≦1), LiAl x Zr 2-x (PO4)3 (where 0≦x≦1, 0≦y≦1), LiTi x Zr 2-x The material may include at least one selected from the group consisting of (PO4)3 (where 0≦x≦1, 0≦y≦1), LISICON-based compounds, LIPON-based compounds, perovskite-based compounds, Nasicon-based compounds, and LLZO-based compounds, but is not limited thereto.
[0086] The sulfide-based solid electrolyte material may be the sulfide-based solid electrolyte represented by Chemical Formula 2 above, but is not particularly limited thereto.
[0087] The present invention also provides a secondary battery having the above structure. The present invention also provides a battery module including the secondary battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include, but are not limited to, a power tool powered by an electric motor; electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.
[0088] Specific examples of the present invention are presented below. However, the examples described below are merely for the purpose of specifically illustrating or explaining the present invention, and the present invention is not limited thereby. Furthermore, the contents not described here can be sufficiently inferred by a person skilled in the art, and therefore the description thereof will be omitted.
[0089] Example 1: Preparation of composite sulfide-based solid electrolyte (1) Lithium halide, LiBr, was prepared, and then placed in a vacuum oven to remove the internal moisture and vacuum dried at 80°C for 24 hours.
[0090] (2) 5 g of LiBr from which moisture had been removed was placed in a ball mill containing 20 zirconia balls (diameter: 10 mm), and high-energy ball milling was performed at a rotation speed of 750 rpm for 15 minutes (one cycle). A total of 16 cycles of ball milling were performed to obtain pulverized LiBr.
[0091] (3) In a glove box, the crushed LiBr and Li6PS5Cl, a sulfide-based solid electrolyte having an argyrodite crystal structure, were mixed in a content ratio of 5 parts by weight:95 parts by weight, and the mixture was mixed to prepare a composite sulfide-based solid electrolyte.
[0092] Example 2: Preparation of composite sulfide-based solid electrolyte A composite sulfide-based solid electrolyte was prepared in the same manner as in Example 1, except that ground LiBr and Li6PS5Cl, a sulfide-based solid electrolyte having an argyrodite crystal structure, were mixed in a content ratio of 10 parts by weight:90 parts by weight.
[0093] Example 3: Preparation of composite sulfide-based solid electrolyte A composite sulfide-based solid electrolyte was prepared in the same manner as in Example 1, except that ground LiBr and Li6PS5Cl, a sulfide-based solid electrolyte having an argyrodite crystal structure, were mixed in a content ratio of 15 parts by weight:85 parts by weight.
[0094] Comparative Example 1: Production of sulfide-based solid electrolyte containing no lithium halide Unlike Examples 1 to 3, a solid electrolyte was produced using only the sulfide-based solid electrolyte Li6PS5Cl having an argyrodite crystal structure that does not contain lithium halide.
[0095] [Experimental Example 1: EDX (Energy dispersive X-ray spectroscopy) analysis of composite sulfide-based solid electrolyte] In order to measure the S element and Br element content contained in the composite sulfide-based solid electrolyte produced in Example 1, an EDX (Energy dispersive X-ray spectroscopy) experiment was carried out, and the results are shown in Figures 4 and 5. The EDX measurement was carried out using a JEOL JSM7900F.
[0096] 4 and 5, in the case of the composite sulfide-based solid electrolyte according to Example 1 of the present invention, it was found that LiBr was not formed as a coating layer of the sulfide-based solid electrolyte, but fine particle size LiBr was located between primary particles of the sulfide-based solid electrolyte.
[0097] [Experimental Example 2: Measurement of ionic conductivity of composite sulfide-based solid electrolyte and analysis of ionic conductivity decrease rate] The composite sulfide-based solid electrolytes according to Examples 1 to 3 and the sulfide-based solid electrolyte according to Comparative Example 1 were each analyzed by measuring the ionic conductivity and the rate of decrease in ionic conductivity due to exposure to moisture.
[0098] (1) Ionic conductivity measurement The composite sulfide-based solid electrolytes according to Examples 1 to 3 and the sulfide-based solid electrolyte according to Comparative Example 1 were each prepared as a test piece having a diameter of 6 mm and a thickness of 1 mm, and were sandwiched between Al-C current collectors and vacuum sealed in an aluminum pouch to prepare an all-solid-state battery.
[0099] The solid-state battery was fastened to a fixture and a pressure of 250 MPa was applied, and the ionic conductivity was measured using impedance spectroscopy. The results are shown in Table 1 below.
[0100] Referring to Table 1, in the case of the composite sulfide-based solid electrolytes of Examples 1 to 3, it was confirmed that the ionic conductivity of the entire composite sulfide-based solid electrolyte was not significantly decreased even if LiBr was further contained between the primary particles of the sulfide-based solid electrolyte.
[0101] This is because by mixing lithium halides such as LiBr into fine particles and mixing them with a sulfide-based solid electrolyte, the LiBr reacts with lithium ions (Li + It can be predicted that this is because the transfer path of ions was not obstructed, and as a result, the conduction of lithium ions was not significantly affected.
[0102] (2) Ion conductivity decrease rate measurement 2 g of each of the composite sulfide-based solid electrolytes according to Examples 1 to 3 and the sulfide-based solid electrolyte according to Comparative Example 1 was evenly spread on a plate and exposed to a dry room environment with a dew point of -45°C (21°C reference humidity 0.46%) for a total of 5 hours, and the rate of decrease in ionic conductivity of the solid electrolyte over time was measured, and the results are shown in Table 1 and Figures 6 and 7 below. Figure 7 is a graph showing normalized ionic conductivity of only the pure sulfide-based solid electrolyte, obtained by removing the rate of change in ionic conductivity due to LiBr from the ionic conductivity measurement results shown in Figure 6.
[0103] The measurement of ionic conductivity at each time was carried out in the same manner as in "(1) Measurement of ionic conductivity" above.
[0104] 6 and 7, the composite sulfide-based solid electrolytes according to Examples 1 to 3 contain lithium halide in a fine particle state capable of absorbing moisture in the solid electrolyte, and thus have improved moisture resistance and a smaller rate of decrease in ionic conductivity of the solid electrolyte over time, as compared with the solid electrolyte according to Comparative Example 1.
[0105] [Table 1]
[0106] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the following claims also belong to the scope of the present invention. [Explanation of symbols]
[0107] 10: Primary particles of sulfide-based solid electrolyte 20: Lithium halide 30: Secondary particles of composite sulfide-based solid electrolyte 40: Sulfide solid electrolyte 100: Composite sulfide solid electrolyte 200: Sulfide solid electrolyte
Claims
1. A plurality of primary particles and secondary particles including a lithium halide represented by the following formula 1: The primary particles include a sulfide-based solid electrolyte, The lithium halide is located between the primary particles. Composite sulfide solid electrolyte: [Chemical formula 1] LiX (In the above formula 1, X is any one selected from F, Cl, Br and I).
2. The average particle size (D50) of the lithium halide is 0.01 to 3 μm. The composite sulfide-based solid electrolyte according to claim 1 .
3. The average particle size (D50) of the secondary particles of the composite sulfide-based solid electrolyte is 0.11 to 100 μm. The composite sulfide-based solid electrolyte according to claim 1 .
4. Based on a total of 100 parts by weight of the composite sulfide-based solid electrolyte, The content ratio of the sulfide-based solid electrolyte and the lithium halide in the primary particles is 99.9 parts by weight:0.1 parts by weight to 80 parts by weight:20 parts by weight. The composite sulfide-based solid electrolyte according to claim 1 .
5. The sulfide-based solid electrolyte includes an argyrodite crystal structure. The composite sulfide-based solid electrolyte according to claim 1 .
6. The average particle size (D50) of the primary particles is 0.1 to 15 μm. The composite sulfide-based solid electrolyte according to claim 1 .
7. In the composite sulfide-based solid electrolyte of the secondary particles, The lithium halide is not formed as a coating layer on the primary particles; The composite sulfide-based solid electrolyte according to claim 1 .
8. The sulfide-based solid electrolyte of the primary particles is represented by the following chemical formula 2: The composite sulfide-based solid electrolyte according to claim 1: [Chemical formula 2] Li k M 1 l S m X 1 n (In the above Chemical Formula 2, M 1 is Sn, Mg, Ba, B, Al, Ga, In, Si, Ge, Pb, N, P, As, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W, or La; 1 is F, Cl, Br, I, Se, Te, or O, and 0<k≦6, 0<l≦6, 0<m≦6, and 0≦n≦6.
9. An all-solid-state battery comprising the composite sulfide-based solid electrolyte according to any one of claims 1 to 8.
10. preparing a sulfide-based solid electrolyte and a lithium halide represented by the following Chemical Formula 1; grinding the lithium halide; mixing the pulverized lithium halide with the sulfide-based solid electrolyte; [Chemical formula 1] LiX (In the above formula 1, X is any one selected from F, Cl, Br and I).
11. The lithium halide may be further dried in a vacuum to remove moisture from the lithium halide before being pulverized. The method for producing the composite sulfide-based solid electrolyte according to claim 10.
12. The lithium halide is pulverized through a ball mill, the ball milling being repeated for 5 to 20 cycles at 100 to 2,000 rpm for 5 to 30 minutes as one cycle. The method for producing the composite sulfide-based solid electrolyte according to claim 10.
13. The average particle size (D50) of the pulverized lithium halide is 0.01 to 3 μm. The method for producing the composite sulfide-based solid electrolyte according to claim 10.
14. The pulverized lithium halide and the sulfide-based solid electrolyte are mixed in a content ratio of 99.9 parts by weight:0.1 parts by weight to 80 parts by weight:20 parts by weight based on a total of 100 parts by weight of the composite sulfide-based solid electrolyte. The method for producing the composite sulfide-based solid electrolyte according to claim 10.
Citation Information
Patent Citations
The glassy solid conductive electrolyte cations
JP1985501731A
Sulfide-based solid electrolyte composition
JP2013143338A
Solid electrolyte for all-solid battery and manufacturing method of the same
JP2022171151A
Lithium-ion rechargeable battery
JP4578684B2
Sulfide Solid Electrolyte and Battery
US20210028486A1